Verniciflavanol A, a profisetinidin-type-4-arylflavan-3-ol from toxicodendron vernicifluum protects SH-SY5Y cells against H2O2-Induced oxidative stress. (January 2023) - Li, Meichen; Zhang, Yunqiang; Han, Tingting; Guan, Lu; Fan, Dongxue; Wu, Qinke; Liu, Jianyu; Xu, Yongnan; Fan, Yanhua
Abstract: Eleven undescribed derivatives of flavan, including flavan-3, 4-diols vernicinosides A-H and profisetinidin-type-4-arylflavan-3-ols verniciflavanols A-C, together with eight known compounds were purified from the heartwood of Toxicodendron vernicifluum. The chemical structures of the undescribed compounds were characterized by spectroscopic data interpretation, including NMR ( 1 H and 13 C NMR HSQC and HMBC) and HRESIMS analysis. CD data analysis was conducted to assign the absolute configurations of the undescribed compounds and the active compound verniciflavanol A was also confirmed by ECD experiment. The absolute configuration of the sugar moiety was identified by GC analysis of chiral derivatives in the hydrolysate. MTT assay was applied to test these compounds against H2 O2 -induced oxidative stress in human neuroblastoma SH-SY5Y cells. Results found that verniciflavanol A demonstrated the best potential in protecting SH-SY5Y cells against H2 O2 -induced oxidative stress by inhibiting cell apoptosis and attenuate reactive oxygen species (ROS) level and mitochondrial dysfunction. And the underlying mechanism was confirmed to be associated with Nrf2-antioxidant response element signaling and IL-6 cell survival pathways. Graphical abstract: Image 1 Highlights: Eleven undescribed flavanols were isolated from Toxicodendron vernicifluum. Verniciflavanol A showed the best antioxidant effect. The mechanism of verniciflavanol A on antioxidant was discussed. Profisetinidin-4-arylflavan-3-ol was investigated on neuroprotective effect firstly.